Antecedents and Consequences Of Green Intellectual Capital On Operational Performance In Coffee Shops At West Jakarta - Rayhan Fadillah; Gatri Lunarindiah (Akuntansi dan Ekonomi Pajak: Perspektif Global, 2024)
This research aims to analyze the influence of Green Intellectual Capital on operational performance in coffee shops in the West Jakarta area. This research uses quantitative methods and uses purposive sampling techniques. Through a questionnaire as a data collection tool, a sample size of 302 respondents was obtained. Questionnaires were distributed to managers, supervisors and baristas in coffee shops using Google Form. Hypothesis testing was carried out using the Structural Equation Model (SEM) method. The research results reveal that Green Intellectual Capital has a positive effect on Operational Performance and significantly on Green Supply Chains Management. Meanwhile, the results of hypothesis testing regarding the influence of Green Supply Chains Management on Operational Performance also provide positive results. These findings may indicate that Green Supply Chains Orientations and environmentally friendly practices in coffee shops are still limited and have not had a significant impact on performance. Based on the research results, managerial implications underline the importance of increasing awareness among coffee shop managers and employees of environmental issues. This awareness is very important to ensure that Green Supply Chains Management in coffee shops is carried out in an environmentally friendly manner, thereby improving operational performance and contributing to the preservation of the natural environment.